PENGEMBANGAN MEDIA MATCHING BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK KELAS 1 MADRASAH IBTIDAIYAH DI BANTUL - Putri Ratna Rosari; Umi Faizah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2025)
The background of this research problem is the difficulty of reading and writing in grade 1 MI children, this is caused by various factors including the child is still young and the reading ability is still low. Therefore, the researcher provides a solution in the form of developing Matching Book media to find out the design of Matching Book media development to improve reading skills in grade 1 children at MI Tahfidz HDWR Brajan Wonokromo Pleret Bantul Yogyakarta, to find out the use of Matching Book media in learning at MI Tahfidz HDWR Brajan Wonokromo Pleret Bantul Yogyakarta, to find out the feasibility of Matching Book media to improve reading skills in grade 1 children at MI Tahfidz HDWR Brajan Wonokromo Pleret Bantul Yogyakarta. This study uses the RnD method. The results of the study that the design of the Matching Book media development makes designs, makes game designs or methods, prints all designs, bound using a spiral and the media is ready to use, the use of Matching Book media as follows conditioning students, introducing letters and simple words, introducing matching images, guiding students to use Matching Book media, the feasibility and potential for developing Matching Book learning media is proven to be suitable for use as a medium to improve the reading skills of grade 1 students. Based on the results of responses and observations in the field, Matching Book media has the potential to be developed and produced.